Impact of Anti-Aggregant, Anti-Coagulant and Non-Steroidal Anti-Inflammatory Drugs on Hospital Outcomes in Patients with Peptic Ulcer Bleeding - Solakoglu, Tevfik (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND/AIMS: There are a limited number of studies including the impact of antiplatelet drugs use on hospital outcomes for nonvariceal upper gastrointestinal bleeding. The aim of this study was to determine the effect of anti-aggregant, anti-coagulant and non-steroidal anti-inflammatory drugs upon hospital outcomes in patients with peptic ulcer bleeding. MATERIALS AND METHODS: The patients under treatment with antiaggregant, anticoagulant or non-steroidal anti-inflammatory drugs were categorized as exposed group (n = 118) and the patients who were not taking any of these drugs were categorized as non-exposed group (n = 81). We analyzed the data of drug intake, comorbid disease, blood transfusion, duration of hospital stay, Blatchford/total Rockall score and diagnosis of patients. RESULTS: In total, 199 patients were included. Of these 59.3% (exposed group) were taking drugs. The patients in exposed group were significantly older than those in non-exposed group (62.9 ± 17.3 years; 55.5 ± 19.3 years, P = 0.005, respectively). Mean number of red blood cell units transfused (2.21 ± 1.51; 2.05 ± 1.87, P = 0.5), duration of hospital stay (3.46 ± 2.80 days; 3.20 ± 2.30 days, P = 0.532) and gastric ulcer rate (33% vs 23.4%, P = 0.172) were higher in exposed group than in non-exposed group but the differences were not statistically significant. Total Rockall and Blatchford scores of the patients were significantly higher in exposed group than in non-exposed group (3.46 ± 1.72 vs 2.94 ± 1.87, P = 0.045; 10.29 ± 3.15 vs 9.31 ± 3.40, P = 0.038). CONCLUSİON: Our study has shown that anticoagulants, antiaggregants and nonsteroidal anti-inflammatory drugs do not effect duration of hospital stay, red blood cell transfusion requirement and rebleeding for peptic ulcer bleeding.